Redesigning of 4 (Four) Blades Propeller Installed in a Wooden Fishing Boat in a Ship Yard in Tegal, Central Java Province - Rifky Ismail; Mohammad Tauviqirrahman; Deni Mulyana; Fiki Firdaus; J. Jamari (Bogor Agricultural University, 2019)
For design of marine propeller, the energy supply from marine engine to the propeller should be converted to thrust force with minimum losses. Furthermore, the unwanted vibration and cavitation due to the overlooking a detail calculation of the propeller should be prohibited for increasing the fuel efficiency and life-span of the propeller. In the last few decades, most of small and medium sized enterprises (SMEs) focusing their work on ship component industry in Central Java Province Indonesia provide the marine propeller to the ship manufacturer and ship repairmen in some shipyards in northern part of Central Java port. The design of the propeller is never been observed and optimized. The aim of the present work is to redesign the installed propeller on a wooden fishing boat with the new optimized design using B-Series propeller theory approach. The reverse engineering method uses three-dimensional scanner to obtain the geometrical data of the installed ship propeller. The new optimized propeller design is obtained from free software calculation based on the boat and engine specification. The comparison shows that the new optimized propeller design has a wider blade and larger pitch and increases 20% of the open water efficiency of the propeller performance at lower engine rotation. Keywords: B-series design, fishing boat, marine propeller, redesign, optimization